Case of hypokalemic paralysis due to use of drug containing therapeutic doses liquorice root - A. F. Vasilenko; M. I. Karpova; A. N. Sergeitsev; R. Iu. Zaliautdinova (Нервно-мышечные болезни, 2020)
The administration of licorice root or licorice preparations (lat. – Glycyrrhiza glabra) is one of the rare causes of hypokalemia. The main active component of licorice is glycyrrhizic acid has mineralocorticoid-like effects. Hypokalemia caused by long-term use of glycyrrhizic acid drugs leads to the development of pseudohyperaldosteronism syndrome including arterial hypertension, metabolic alkalosis and muscle weakness. In this publication we present the clinical case of severe hypokalemia due to use of the drug “Phosphogliv”, containing the trisodium salt of glycyrrhizic acid as one of the active substances. The specific feature of the case given is that the complication was caused using the therapeutic dosage of the drug.